Handbook of ecotoxicology - Calow, Peter (Blackwell, 1998)
General principles and overview - Microbial systems - Freshwater primary producers - Freshwater invertebrate toxicity tests - Freshwater fish - Freshwater sediments - Freshwater multi-species test systems - Primary producers - Marine and estuarine invertebrate toxicity tests - Methods for spawning, culturing and conducting toxicity tests with early life stages of estuarine and marine fishes - Appropriate uses of marine and estuarine sediment bioassays - Marine and estuarine multi-species test systems - Soil invertebrates and micro-organisms - Terrestrial primary producers - Insects, spiders and mites - Birds - Terrestrial mammals - Biodegradation - Bioaccumulation - In situ biological monitoring of pollution in terrestrial and aquatic ecosystems - Bioprobes and biosensors - The design and analysis of concentration. Response experiments - Overview with observations on risk assessment and management - Gaseous comounds - Acid solutions - Metal analysis - Heavy metals - Organometallic compounds in the aquatic environment - Detergents - Pesticides - PCBs, PCDDs and PCDs - Oils and hydrocarbons - Organic pollution: biochemical oxygen demand and ammonia - Complex mixtures - The octanol-water partition coefficient - Quantitative structure. Activity relationships - Fate models - Prioritization and standards for hazardous chemicals.